Interações rural-urbano: a sociobiodiversidade e o trabalho em portos, feiras e mercados de Belém, Pará - SILVA, Iraneide Souza (2015)
Many species that represent Amazonian sociobiodiversity, in addition to their ecological role, also exert an impact on the economy by means of their various usages — alimentary, therapeutic, ornamental or for handicraft — and reflect the productive potential of the islands of the municipality of Belém and other parts of the State of Pará. The promotion of those products boosts the activities in the marts, wharves and marketplaces studied — the Ver-o-Peso Complex, Porto do Açaí, Porto da Palha, the Jurunas Supply Complex and the Icoaraci Riverbank Mart — and insere the reproduction of rural social groups and informal urban workers, who number over a thousand individuals directly involved in their trade, organized either singly or in families, and mostly earning a monthly income of one to three times the minimum wage. It is essential to consider the riverine waterfront of Belém as a place of interaction between the rural and the urban, so as to allow for a critical analysis of the forms of appropriation of the city, or social production and reproduction of the work system, the actors involved and the benefits of sociobiodiversity.